Investigation of the process of depressurization of the hydraulic discharge pipeline - Voskresenskij G.G.; Ivanchenko S.N. (Научно-технический вестник Брянского государственного университета)
In the article the review of devices for protection of hydraulic systems from emergency emissions of working fluid at depressurization of pipelines is given. The information on the influence of hydraulic oil used in the working fluid quality on the environment is presented. It has been established that hydraulic oil spilled on the surface as a result of emergency discharge during depressurization of discharge pipes belongs to the waste of the 3rd hazard class. The period of recovery of the environment after the harmful effects of spilled hydraulic oil is at least ten years and is a violation of environmental and sanitary-epidemiological requirements. A mathematical model has been developed that includes the equations of hydraulic oil flows and leaks from the damaged part of the discharge pipeline, the volume of spilled hydraulic oil, the intensity of pressure changes in the discharge and discharge lines. The results of numerical solution of mathematical models on the impact parameters of the hydraulic system on the dynamics of pressure changes in the injection and drain lines in search of information parameters for building devices that exclude significant loss of working fluid. It is established that the pressure derivative is the information parameter for the creation of the system of protection of the hydraulic system from emergency emissions of hydraulic oil.